Modernization of professional foreign language training for future masters of Ukrainian universities in conditions of inter-ethnic communication - Vasylyshyna, Natalia; Skyrda, Tetiana; Frolova, Olena; Leleka, Tetiana; Horovenko, Oksana (My University, 2022)
Стаття присвячена модернізації професійної іншомовної підготовки майбутніх магістрів та описано систему навчання, яка використовується у закладах вищої освіти України. Метою дослідження є вдосконалення методики фахової іноземної мовної підготовки майбутніх магістрів вищої освіти України. Актуальність дослідження полягає у сфері процесів глобалізації, зокрема розвитку міжнародних відносин. Значущість дослідження підтверджує відсутність наукового праць з методики навчання іноземної мови магістрів, які готуються до міжнаціонального спілкування в практичній діяльності. Результати дослідження формують новизну та практичну цінність, яка виражається у можливості використання методик у освітньому процесі закладів вищої освіти України. На думку авторів, у магістерських програмах вивчення іноземної мови має домінувати проблемно-орієнтований підхід, міждисциплінарний, дуальний, варіативний метод навчання з урахуванням різного рівня володіння здобувачами освіти англійською мовою та з використанням сучасних інструментів цифровізації.The article is devoted to modernizing professional foreign language training of future masters and describes the educational system used in higher educational institutions of Ukraine. The study aims to improve professional foreign language training methods for future masters of higher education in Ukraine. The study's relevance lies in the area of globalization processes, particularly the development of international relations. The significance of the study confirms the lack of scientific research on teaching methods of a foreign language to masters who are preparing for international communication in practical activities. The study results form the novelty and practical value, which is expressed by the possibility of using the techniques in the educational processes of higher education institutions in Ukraine. The authors believe that the problem-oriented approach, interdisciplinary, dual, variant method of teaching taking into account different English levels among students and using modern tools of digitalization should dominate in the master's programs of foreign language study.
Modernization of professional foreign language training for future masters of Ukrainian universities in conditions of inter-ethnic communication / N. Vasylyshyna, T. Skyrda, O. Frolova, T. Leleka, O. Horovenko // AD ALTA : Journal of Interdisciplinary Research, 12/01-XXVI. – 2022. – P. 56–60
Keywords: навчальні стратегії, компетенція, прямі навчальні стратегії, непрямі навчальні стратегії, учні; Іноземна мова, педагогіка, магістерська програма, міжнародна комунікація